Speech act strategies in police interrogation transcripts: evidence from bahasa Indonesia investigative records - M. Ansori (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Police interrogation discourse in Indonesia plays a central role in shaping judicial outcomes, yet its linguistic dynamics remain underexplored in forensic linguistics. Objective: The aim of this study is to investigate speech act strategies, politeness patterns, and discursive structures in official interrogation transcripts (Berita Acara Pemeriksaan) written in Bahasa Indonesia. Method: This research employed a qualitative descriptive design, analyzing a corpus of interrogation records and trial excerpts using Speech Act Theory, Politeness Theory, and Forensic Discourse Analysis. Results: The results show that directive and assertive speech acts dominate interrogators’ language, while commissives and expressives are more common in suspects’ responses. Politeness strategies reveal a strong preference for bald on record forms by interrogators, contrasted with suspects’ reliance on positive and negative politeness to mitigate pressure. Discursive structures demonstrate institutional asymmetry, with interrogators controlling turns, topics, and narrative framing to legitimize official accounts. These findings confirm that interrogation discourse functions more as a tool of institutional authority than as a neutral exchange. Implication: The implication of this research is the need for greater awareness of linguistic power in legal processes and the incorporation of forensic linguistic insights into interrogation practices and justice reform. Novelty: This study reveals how interrogation discourse in Indonesia is systematically structured to reinforce institutional authority through asymmetric speech acts, politeness strategies, and narrative control.